BE-RAISE: A Blended-Learning Model Based on Balinese Local Culture to Enhance Student’s Environmental Literacy - Hermawan, I. M. S.; Arjaya, I. B. A.; Diarta, I. M. (Jurnal Pendidikan IPA Indonesia, 2022)
Environmental education through strengthening environmental literacy is needed in the era of technological advances and globalization to ensure environmental sustainability in the future. This study aims to develop the BE-RAISE learning model to improve students’ environmental literacy. BE-RAISE is a blended learning model based on the Tri Hita Karana culture that the Balinese people embrace. This is research and development using the Plomp development model. The steps consist of preliminary research, prototyping phase, and assessment phase. This research involved two biology learning experts, one learning technology expert, two teachers, and 36 students. Data on the validity, practicality, student responses, and effectiveness of the BE-RAISE learning model were collected in this study. The data collection instruments used were validity and practicality sheets, student response questionnaires, and environmental literacy tests. Data analysis of validity, practicality, and student responses was carried out by descriptive analysis. Meanwhile, the learning model effectiveness was analyzed using t-paired, which had previously been tested for normality and homogeneity. The results showed that the BE-RAISE learning model was declared valid and practical, received a positive response from students, and was effective in improving environmental literacy (p0.05). Therefore, it can be concluded that the BE-RAISE learning model is declared feasible to be used in the learning process to improve environmental literacy. Further research is needed to reveal the effect of the BE-RAISE learning model on environmental literacy by design using a comparison unit and to reveal its effect on students’ critical thinking skills and problem-solving skills.